MODEL KEBUTUHAN PENGOPERASIAN ANGKUTAN ANTAR JEMPUT (CARPOOLING) BAGI SISWA SEKOLAH DI KOTA DENPASAR - Dewa Ayu Nyoman Sriastuti; A.A. Rai Asmani. K; A.A.Gde Sumanjaya (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
Based on previous research, it is necessary to do further research to get the linkages between various variables that influence the need for operation of this shuttle transportation, by taking the title "Model of Operation Needs of Shuttle (Carpooling) for School Students in the City of Denpasar", where in this study the transport demand variable modeled is the relationship between the interest of parents of students using school shuttle as a dependent variable and tariff variable, capacity and travel time as a free variable. The data and information that you want to know from the survey on the respondent is to determine the interest in using school shuttle, the weight of the tariff factor (X1), capacity (X2) and travel time (X3). The data and information obtained were then analyzed by the Regression method using the help of the SPSS program software. This study provides an overview of the relationship model between interest-dependent variables (Y) using school shuttle transportation with tariff-free variables (X1), vehicle capacity (X2) and travel time (X3) as stated by the regression equation Y = 0.825 - 0.395X1 - 0.562X2 - 0.295X3 and the most dominant variable affecting the interest of parents of students to use shuttle (Carpooling) as a means of school transportation is the variable rate with an Exp (B) value of 1.43.